1999
DOI: 10.1074/jbc.274.52.37240
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Histo-blood Group ABO Genes Is Dependent upon DNA Methylation of the Promoter Region

Abstract: We have investigated the regulatory role of DNA methylation in the expression of the human histo-blood group ABO genes. The ABO gene promoter region contains a CpG island whose methylation status correlates well with gene expression in the cell lines tested. The CpG island was found hypomethylated in some cell lines that expressed ABO genes, whereas the other cell lines that did not express ABO genes were hypermethylated. The ABO blood group system discovered by Karl Landsteiner (1) at the beginning of this ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 45 publications
3
100
0
2
Order By: Relevance
“…Reportedly, the promoter region of the ABO gene is located between À117 and þ 31 from the translation start site, of which hypermethylation regulates gene expression. 19,20 In the present study, we divided CpG island spanning À789 to þ 6 into six regions and examined the methylation status by BiPS analysis (Figure 2). In the preliminary experiment, methylated DNA could be identified as the extra band, if more than 25% of the template DNA was methylated (data not shown).…”
Section: Methylation Status Of the Abo Gene Promoter Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, the promoter region of the ABO gene is located between À117 and þ 31 from the translation start site, of which hypermethylation regulates gene expression. 19,20 In the present study, we divided CpG island spanning À789 to þ 6 into six regions and examined the methylation status by BiPS analysis (Figure 2). In the preliminary experiment, methylated DNA could be identified as the extra band, if more than 25% of the template DNA was methylated (data not shown).…”
Section: Methylation Status Of the Abo Gene Promoter Regionmentioning
confidence: 99%
“…Recent advance in cancer epigenetics shed light on the reduced expression of A antigen in malignant cells. Kominato et al 19,20 reported that hypermethylation of the promoter region of the ABO gene induced ABO gene silencing in their study using a human stomach carcinoma cell line. Iwamoto et al 21 established subclones with positive or negative expression of the A antigen from parental colonic cancer cell lines and reported a distinct difference in the methylation pattern of the CpG island of the promoter region of the ABO glycosyltransferase, that is densely methylated in a subclone lacking the expression of the A antigen.…”
mentioning
confidence: 99%
“…Rat chemical-induced colorectal cancer also changed the ABH antigen expression (13). The ABH gene expression was down-regulated in A-negative human colorectal cancer cells by the methylation of the promoter and the reduced activity of the enhancer element of the gene (31,32). The presented cDNA data should contribute for investigation in alteration of the rat ABO homologue expression in the chemical oncogenesis.…”
Section: A-or B-antigen Expression In Wild A-tg and B-tg Rats-to Acmentioning
confidence: 99%
“…PCR was carried out using the HotStarTaq Kit (Qiagen); the annealing temperatures for the unmethylated and methylated reactions were 60 and 621C, respectively. Primer sequences and reaction conditions for MS-PCR analysis of the ABO gene promoter were as described (Kominato et al, 1999;Gao et al, 2004). The PCR products were resolved on 2% agarose gels.…”
Section: Methylation Analysismentioning
confidence: 99%